KAJIAN AKUNTANSI KOPERASI SIMPAN PINJAM /UNIT SIMPAN PINJAM PROVINSI JAWA TIMUR - Hadijono, Sri; RATNAWATI, TRI; Trihastuti, Adiati (JEA17: Jurnal Ekonomi Akuntansi, 2019)
ABSTRACTSavings and Loan Cooperatives or KSP and Savings and Loans Unit or USP is a cooperative whose capital is obtained from principal savings and mandatory savings and others from cooperative members. The capital that has been collected is then lent to members and prospective cooperative members who need a loan. To each borrower, the savings and loan cooperative or KSP attracts interest on loans and administrative costs. Because the deposits and loans are from members to members, the flow of money in and the flow of money out must be really made and must be carried out with discipline, meaning that it must be recorded and recorded in an orderly manner. Healthy cooperatives are cooperatives that are managed professionally, meaning all funds and power must be optimized for smoothness and added value for the cooperative. Therefore KSP / USP management must pay attention to the needs of their employees must base the required competencies. Healthy cooperatives certainly every certain period report the performance results of management in the form of financial statements.Keywords: Healthy KSP / USP, Cash Flow Discipline and orderly accounting